PROTECTION OF CARBON STEEL FROM WEAR BY QUENCHING WITH NANOTECHNOLOGY TO USE IT IN DIES PARTS - Hafedh, Khalid Abdulhussein; Ibrahim, Zaman Khalil; Razooqi, Ahmed Ibrahim; Mohammed, Malik M.; Alalwan, Hayder (Journal of Applied Engineering Science, 2023)
Adding nanomaterials to quenching media is an innovative method to alter alloys’ mechanical properties and enhance their resistance to wear. In this work, TiO2 nanoparticles were added to the oil as a quenching media in different mass percentages (0, 0.2, 0.4, and 0.6%) to identify the impact of adding TiO2 nanoparticles on wear resistance (dry sliding) and mechanical properties by microstructure analysis of carbon steel CK45 before and after the addition of nanofluid. The results reveal the critical role of adding nanomaterials in altering steel’s mechanical properties and increasing its resistance to wear. Specifically, increasing the TiO2 nanoparticle percentage improves the wear resistance value under different loads (20, 30, and 40 N). Also, the homogenous microstructure and mechanical properties were enhanced after using nanotechnology. That means the nanotechnology can protect CK45 from wear to be used for dies structure parts by quenching process.